Accuracy of Otolith Oxygen Isotope Records Analyzed by SIMS as an Index of Temperature Exposure of Wild Icelandic Cod (Gadus morhua) - von Leesen, Gotje; Bardarson, Hlynur; Halldórsson, Sæmundur Ari; Whitehouse, Martin J.; Campana, Steven E. (Frontiers in Marine Science, 2021)
Global warming is increasing ocean temperatures, forcing marine organisms to respond to a suite of changing environmental conditions. The stable oxygen isotopic composition of otoliths is often used as an index of temperature exposure, but the accuracy of the resulting temperature reconstructions in wild, free-swimming Atlantic cod (Gadus morhua) has never been groundtruthed. Based on temperatures from data storage tags (DST) and corresponding salinity values, the stable oxygen isotope (δ18O) value was predicted for each month of tagging and compared with δ18Ootolith values measured in-situ with secondary-ion mass spectrometry (SIMS). Paired-sample Wilcoxon tests were applied to compare measured and predicted δ18O values. The difference between measured and predicted mean and maximum δ18Ootolith values was not significant, suggesting a good correspondence between SIMS-measured and DST-predicted δ18Ootolith values. However, SIMS-measured and predicted minimum δ18Ootolith values were significantly different (all samples: p < 0.01, coastal and frontal cod: p < 0.05), resulting in overestimation of maximum temperatures. Our results confirm that otoliths are well-suited as proxies for mean ambient temperature reconstructions. A possible matrix effect and the absence of a reliable aragonite standard for SIMS measurements appeared to cause a small divergence between measured and predicted δ18Ootolith values, which affected the estimation accuracy of absolute temperature. However, relative temperature changes were accurately estimated by SIMS-analyzed δ18Ootolith values.